2015
DOI: 10.5032/jae.2015.01172
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Agriculture Teachers' Perceived Level of Readiness in an Agricultural Mechanics Course

Abstract: This longitudinal trend study sought to compare the perceptions of preservice agricultural education teachers, enrolled in a Metals and Welding course at a land grant university, on their welding related skills at the beginning of the semester to their final course grade at the end of the semester. Preservice agriculture teachers (N = 240) who completed the course between the Fall 2006 and Spring 2012 semesters served as the population for the study. Although the course is designed, specifically, to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Agricultural mechanics knowledge issues are compounded by a lack of adequate training, professional development, and instructional materials in agricultural safety (Rudolphi & Retallick, 2015). Specifically, agricultural programs have reduced the amount of training received in courses specific to agricultural mechanics (Burris et al, 2005;Schumacher, Ess, Strickland, & King, 2002), and teachers across multiple geographic regions and teaching experience levels have reported a need for professional development related to agricultural mechanics (Blackburn, Robinson, & Field, 2015;Duncan, Ricketts, Peake, & Uesseler, 2006;Stripling et al, 2014). Among the many professional development needs of agricultural mechanics teachers, safety instruction and supervision is a top concern while in the agricultural mechanics laboratory (Gliem & Miller, 1993;Johnson & Schumacher, 1988;Langley & Kitchel, 2013;Swan, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural mechanics knowledge issues are compounded by a lack of adequate training, professional development, and instructional materials in agricultural safety (Rudolphi & Retallick, 2015). Specifically, agricultural programs have reduced the amount of training received in courses specific to agricultural mechanics (Burris et al, 2005;Schumacher, Ess, Strickland, & King, 2002), and teachers across multiple geographic regions and teaching experience levels have reported a need for professional development related to agricultural mechanics (Blackburn, Robinson, & Field, 2015;Duncan, Ricketts, Peake, & Uesseler, 2006;Stripling et al, 2014). Among the many professional development needs of agricultural mechanics teachers, safety instruction and supervision is a top concern while in the agricultural mechanics laboratory (Gliem & Miller, 1993;Johnson & Schumacher, 1988;Langley & Kitchel, 2013;Swan, 1992).…”
mentioning
confidence: 99%
“…Females comprise about half of recent student teaching populations (Burris et al, 2010;. Specific to agricultural mechanics preservice preparation, Blackburn et al (2015) reported one-third of the students enrolled in a preservice agricultural mechanics course from 2006 to 2012 were female.…”
mentioning
confidence: 99%
“…Instruction in metal fabrication requires technical and administrative procedures, tools, equipment, laboratory arrangement, consumable materials, and quality assurance (Yakubu, 2014). To ensure SBAE teachers are technically competent, teacher preparation programs should engage preservice teachers in agricultural mechanics courses to prepare them to teach specific skills necessary for future employment (Blackburn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although agricultural mechanics has been integrated with or closely related to agricultural education for several years (Thoron, Myers, & Barrick, 2016) numerous agriculture teacher preparation programs require preservice teachers to complete relatively few credit hours of agricultural mechanics courses for graduation (Blackburn et al, 2015). As noted by Burris et al (2005), a majority of teacher preparation programs required fewer than 12 hours in agricultural mechanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation